Resale price maintenance in European Competition Law: Background, developments and prospects - Velasco San Pedro, Luis Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The object of this article is resale price maintenance in European competition law. Firstly, the anti- and pro-competitive effects of this practice are studied, as well as the evolution of its regulation in the United States, as a reference model, up to the Leegin judgment. The situation in the EU is then analysed, based on how the issue has been historically considered in the block exemption regulations and by the Commission’s practice and the case law of the Court of Justice. Finally, the current state of the matter is studied in Regulation 2022/720 on vertical agreements, the 2022 Commission Communication on Guidelines on vertical restraints and the recent judgment of the Court of Justice in the Super Bock case.
Keywords: Resale price maintenance; RPM; vertical agreements; European Competition Law; interbrand competition